Digesti Logam Zink(Zn) Dalam Sedimen Estuaria Sungai Palu Dengan Kombinasi Asam Mineral - Galib, Stefhanny; Said, Irwan; Napitupulu, Mery (Jurnal Akademika Kimia, 2017)
The research was conducted to determine the digestion power is highest of Zn metal with the combination of mineral acids in the estuarine sediments of Palu River samples. Zn metal concentrations in the sediments were analysed by Atomic Absorption Spectroscopy (AAS) at a wavelength of 231.9 nm. The results showed that water content ranged between 30.36%-37.18%, ash content ranged from 52.40%-68.76%, and biomass content ranged from 0.88%-10.42%. Analysis of AAS showed the significant average of Zn metal on a combination of mineral acids HNO3-H2SO(1:1) was 289.95182.49 mg/kg, and on a combination of mineral acids HNO3-HCl (1:3) was 669.18447.2 mg/kg. While calculation results of the relative standard deviation values were 25.35% for the combination of mineral acids HNO3-H2SO4 (1:1), and 22% for the combination of mineral acids HNO3-HCl (1:3). The combination of mineral acids having the highest digestion to the Zn metal in the estuarine sediments of Palu River was a combination of mineral acids HNO3-HCl (1:3).